Hydrodynamic characterization and performance evaluation of an aerobic three phase airlift fluidized bed reactor in a recirculation aquaculture system for Nile Tilapia production - Sanchez O, Ivan Andres; Matsumoto, Tsunao [UNESP] (Elsevier B.V., 2012)
The hydrodynamic characterization and the performance evaluation of an aerobic three phase fluidized bed reactor in wastewater fish culture treatment are presented in this report. The objective of this study was to evaluate the organic matter, nitrogen and phosphorous removal efficiency in a physical and biological wastewater treatment system of an intensive Nile Tilapia laboratory production with recirculation. The treatment system comprised of a conventional sedimentation basin operated at a hydraulic detention time HDT of 2.94 h and an aerobic three phase airlift fluidized bed reactor AAFBR operated at an 11.9 min HDT. Granular activated carbon was used as support media with density of 1.64 g/cm(3) and effective size of 0.34 mm in an 80 g/L constant concentration. Mean removal efficiencies of BOD, COD, phosphorous, total ammonia nitrogen and total nitrogen were 47%, 77%, 38%, 27% and 24%, respectively. The evaluated system proved an effective alternative for water reuse in the recirculation system capable of maintaining water quality characteristics within the recommended values for fish farming and met the Brazilian standards for final effluent discharges with exception of phosphorous values. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Three phase fluidized bed; Biofilters; Biological treatment; Hydrodynamic characterization; Recirculation; Aerobic reactor